UPAYA PENINGKATAN KOMPETENSI DALAM MEMBUAT MOBILE LEARNING MANAGEMENT SYSTEM (M-LMS) BERBASIS ANDROID BAGI GURU DI SMK NEGERI 1 KOTA JAMBI: M-LMS, Android, Teacher Competence, SMKN 1 City Of Jambi - Rini, Faiza; Purnama, Fery; -, Pariyadi (JURNAL AKADEMIKA, 2018)
M-LMS android is an innovative learning model using internet technology. One of the media or applications that can be used to facilitate learning is to use M-LMS based android. M-LMS based on android implemented to improve teacher competence in SMKN 1 City of Jambi. In 2017 teachers in SMKN 1 city of Jambi on average from their teachers have used android as much as 98% and students who use android as much as 91.82%, 2.24% using IOS, Manual 4% and 1.94% have no android nor IOS. M-LMS android is one of the learning models that will be used in SMKN 1 Kota Jambi. In addition to the learning managerial implemented, M-LMS is able to provide new alternatives about information-based learning media that can be used in the learning process both in the classroom whenever and wherever. Problems can also be solved when a learning model emerges using M-LMS using an android based flatform moodle that can help teachers and students in the learning process whenever and wherever.